IF GOD EXISTS, WHY THE RISE IN THE CASES OF EVIL & CRISIS EXPERIENCED ON EARTH! A Critical Examination of the Problem of Evil & Crisis and Its Impact on the Belief in God! (AUN INTERNATIONAL CONFERENCE, 2025)
The problem of evil continues to be a key impediment to the belief of an all-powerful, all-knowing and all-good God. This research paper explores how theology and philosophy have tried to reconcile God’s nature with the existence of evil and suffering in the world. This paper examines major theodicies such as the free will defence, the soul-making theodicy and Augustinian and Irenaean perspectives, alongside atheistic arguments such as the logical and evidential problems of evil, through a qualitative analysis of classical and modern texts, scriptures and experiential accounts. It also investigates how believers react in the face of evil and suffering. This study finds that while no single explanation eliminates all conflict between divine goodness and worldly suffering, a layered understanding- combining moral freedom, soul development, and faith resilience offers a more nuanced response to this persistent challenge. This paper concludes by affirming that belief in God is still plausible despite the presence of evil, especially when viewed through the lenses of faith, trust, mystery and personal choices.